Analisis Luas Panen, Produktivitas, dan Produksi Tanaman Jagung di Kabupaten Semarang dengan Pendekatan Sistem Informasi Geografis - Badin Firman Gani (CV. KAMPUS AKADEMIK PUBLISING, 2024)
This study analyzes the extent of cultivation, productivity, and production of corn crops in Semarang Regency using the Geographic Information System (GIS) approach. The GIS method is utilized to map the spatial distribution of corn agricultural land, its productivity, and overall production in the Semarang Regency area. Spatial data such as land maps, elevation, rainfall, and soil types are employed in this analysis. The GIS approach facilitates the integration of spatial data with corn crop productivity data. This spatial analysis provides in-depth information on the spatial distribution of cultivation extent, productivity, and production of corn crops in each region of Semarang Regency. The analysis results indicate significant variations in the extent of cultivation, productivity, and production of corn crops in Semarang Regency. Topographic factors, soil types, and rainfall patterns are the main factors influencing corn crop productivity in different areas. The information obtained from this analysis can serve as a basis for decision-making in the development of more efficient and sustainable agricultural strategies in Semarang Regency.